Evaluation of Eucalyptus citriodora essential oil on goat gastrointestinal nematodes Avaliação do óleo essencial de Eucalyptus citriodora sobre nematóides gastrintestinais de caprinos - Iara Tersia Freitas Macedo; Claudia Maria Leal Bevilaqua; Lorena Mayana Beserra de Oliveira; Ana Lourdes Fernandes Camurça-Vasconcelos; Luiz da Silva Vieira; Sthenia dos Santos Albano Amóra (Revista Brasileira de Parasitologia Veterinária, 2011)
Phytotherapy may be an alternative strategy for controlling gastrointestinal parasites. This study evaluated the anthelmintic efficacy of Eucalyptus citriodora essential oil (EcEO). The in vitro effects of EcEO were determined through testing the inhibition of egg hatching and larval development of Haemonchus contortus. EcEO was subjected to acute toxicity testing on mice, orally and intraperitoneally. The in vivo effects of EcEO were determined by the fecal egg count reduction test (FECRT) in goats infected with gastrointestinal nematodes. The results showed that 5.3 mg.mL-1 EcEO inhibited egg hatching by 98.8% and 10.6 mg.mL-1 EcEO inhibited H. contortus larval development by 99.71%. The lethal doses for 50% of the mice were 4153 and 622.8 mg.kg-1, for acute toxicity orally and intraperitoneally. In the FECRT, the efficacy of EcEO and ivermectin was 66.25 and 79.16% respectively, on goat gastrointestinal nematodes eight days after treatment. EcEO showed in vitro and in vivo anthelmintic activity. Fitoterapia pode ser uma estratégia alternativa para o controle de parasitas gastrintestinais. Este estudo avaliou a eficácia anti-helmintica do óleo essencial de Eucalyptus citriodora (OeEc). Os efeitos in vitro do OeEc foram determinados através do teste de eclosão de ovos e inibição do desenvolvimento larvar de Haemonchus contortus. O OeEc foi submetido ao teste de toxicidade aguda oral e intraperitoneal, em camundongos. Os efeitos in vivo do OeEc foram avaliados através do teste de redução da contagem de ovos nas fezes (FECRT) com caprinos infectados com nematóides gastrintestinais. Os resultados mostraram que 5,3 mg.mL-1 OeEc inibiram 98,8% a eclosão de ovos e 10,6 mg.mL-1 OeEc inibiram 99,71% o desenvolvimento larvar de H. contortus. As doses letais para 50% dos camundongos foram de 4153 e 622,8 mg.kg-1 pela via oral e intraperitoneal. No FECRT, a eficácia de OeEc e ivermectina foi de 66,25 e 79,16%, respectivamente, em caprinos 8 dias após o tratamento. OeEc mostrou atividade anti-helmintica in vitro e in vivo.